2010
DOI: 10.1002/hlca.201000074
|View full text |Cite
|
Sign up to set email alerts
|

Four New Lignan Glycosides from Osmanthus fragransLour. var. aurantiacusMakino

Abstract: Four new tetrahydrofuranoid lignan glycosides, (7S,8R,7′R,8′S)‐4,9,4′,7′‐tetrahydroxy‐3,3′‐dimethoxy‐7,9′‐epoxylignan 9‐O‐β‐D‐glucopyranoside (2), (7R,8S,7′S,8′R)‐4,9,4′,7′‐tetrahydroxy‐3,3′‐dimethoxy‐7,9′‐epoxylignan 9‐O‐β‐D‐glucopyranoside (3), (7R,8S,7′R,8′S)‐4,9,4′,9′‐tetrahydroxy‐3,3′‐dimethoxy‐7,7′‐epoxylignan 9‐O‐β‐D‐glucopyranoside (4), and rel‐(7R,8S,7′S,8′R)‐4,9,4′,9′‐tetrahydroxy‐3,3′‐dimethoxy‐7,7′‐epoxylignan 9‐O‐β‐D‐glucopyranoside (5), and ten known lignan glycosides, 1 and 6–14, were isolated f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…During the analysis of the stereochemistry of compounds 1 and 2 as well as other compounds with similar structures such as 7 R ,8 R ,8' S ‐aketrilignoside B, (7 S ,8 R ,7' R ,8' S )‐4,9,4',7'‐tetrahydroxy‐3,3'‐dimethoxy‐7,9'‐epoxylignan 9‐ O ‐β‐D‐glucopyranoside, and 7 S ,7' S ,8 R ,8' R ‐icariol A 2 , it was found that the stereochemistry of C‐7 or C‐7' in monofuranoid lignans affects the signal of CD at around 210 nm. For example, if a CD spectrum has a positive signal at 210 nm, the configurations at C‐7 or C‐7' of lignan were determined to be R .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…During the analysis of the stereochemistry of compounds 1 and 2 as well as other compounds with similar structures such as 7 R ,8 R ,8' S ‐aketrilignoside B, (7 S ,8 R ,7' R ,8' S )‐4,9,4',7'‐tetrahydroxy‐3,3'‐dimethoxy‐7,9'‐epoxylignan 9‐ O ‐β‐D‐glucopyranoside, and 7 S ,7' S ,8 R ,8' R ‐icariol A 2 , it was found that the stereochemistry of C‐7 or C‐7' in monofuranoid lignans affects the signal of CD at around 210 nm. For example, if a CD spectrum has a positive signal at 210 nm, the configurations at C‐7 or C‐7' of lignan were determined to be R .…”
Section: Resultsmentioning
confidence: 99%
“…The positive Cotton effect [Δε: + 1.65 (216)] (Fig. ) in the CD spectrum of 3 proved the configuration at C‐7 to be S by comparing it with those of 7 R lignan glycosides: 7 R ,8 R ,8' S ‐aketrilignoside B [Δε: – 14.0 (215)] (7 R ,8 S ,7' S ,8' R )‐4,9,4',7'‐tetrahydroxy‐3,3'‐dimethoxy‐7,9'‐epoxylignan 9‐ O ‐β‐D‐glucopyranoside [Δε:–12.9 (205), –2.5 (234)], and 7 S lignan glycosides: (7 S ,8 R ,7' R ,8'S)‐4,9,4'‐trihydroxy‐3,5,3',5',7'‐pentamethoxy‐7,9'‐epoxylignan 9‐ O ‐β‐D‐glucopyranoside [Δε: + 15.2 (206), + 3.5 (235)], alangilignoside C [Δε: + 11.1 (211), ‐1.14 (244)] . The small coupling constant J 7‐8 = 3.6 Hz between H‐7 and H‐8 confirmed cis configuration of the substituted groups at C‐7 and C‐8, and it was further proved by strong NOE correlation between H‐7 (δ H 5.13) and H‐8 (δ H 2.52).…”
Section: Resultsmentioning
confidence: 99%
“…The coupling constant of H-7′ ( J = 7.5 Hz) in 1 suggested an antiperiplanar orientation of H-7′ and H-8′. On the other hand, the CD spectrum of 1 (Δε: −121.7 (201 nm), −5.9 (228 nm)) was very similar to that of (7 R ,8 S ,7′ S ,8′ R )-4,9,4′,7′-tetrahydroxy-3,3′-dimethoxy-7,9′-epoxylignan 9- O -β- d -glucopyranoside (Δε: −12.9 (205 nm), −2.5 (234 nm)) [39], which indicated the absolute configuration of 1 was 7 R ,8 S ,7′ S ,8′ R . Furthermore, the NOE correlations between δ H 4.56 (H-7) and δ H 2.40 (H-8′) and 3.75 (H-9a); δ H 1.75 (H-8) and δ H 3.97 (H-7′); and δ H 2.40 (H-8′) and δ H 3.75 (H-9a), 6.64 (H-6′) and 6.76 (H-2′) observed in the NOESY spectrum confirmed the accuracy of configuration analysis.…”
Section: Resultsmentioning
confidence: 74%
“…The six known compounds were identified (Figure 1) as L-phenylalanine ( 1 ) [14], dihydroxymethyl-bis(3,5-dimethoxy-4-hydroxyphenyl) tetrahydrofuran-9- O -β- d -glucopyranoside ( 3 ) [15], rel -(7 R ,8 S ,7′ S ,8′ R )-4,9,4′,9′-tetrahydroxy-3,3′-dimethoxy-7,7′-epoxylignan 9- O- β- d -glucopyranoside ( 4 ) [16], apigenin 6- C- α- l -arabinopyranosyl-8- C- β- d -glucopyranoside ( 5 ) [17], apigenin 7- O ,8- C - di -glucopyranoside ( 6 ) [18], and ( 7S , 8S ) syringylglycerol-8- O -4′-sinapyl ether 9′- O- β- d -glucopyranoside ( 9 ) [19] through comparing their spectroscopic and physical data with those of previous reports.…”
Section: Resultsmentioning
confidence: 99%